2011
DOI: 10.1007/s11095-011-0378-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physical Properties of Biomaterials on Cellular Behavior

Abstract: PurposeIn this study, we evaluated the effect of hydrogel structural properties on proliferation and biosynthesis activity of encapsulated chondrocytes.MethodsHydrogels with varying structural and mechanical properties were prepared by photopolymerizing PEGDA precursors having MWs of 3.4 kDa, 6 kDa, 10 kDa, and 20 kDa and were characterized for their swelling ratio, network structure, morphology, and mechanical properties. The effect of hydrogel structural properties on the cellular activity of encapsulated ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
160
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(176 citation statements)
references
References 28 publications
16
160
0
Order By: Relevance
“…Although polymer chains are relatively less random in LM-PEG, it cannot influence MSC function in a biomimetic manner which indicates that polymer morphology achieved through physical cross-link is an effective mechanism for polymer chain assembly and for promoting bioactive functionality in MSCs. Cellular aggregation and enhanced chondrogenesis in hydrogel is typically achieved with excessive cell density ($10 6 cell Á mL À1 ); [20,32] in our studies, cellular aggregation in PEG-PU gels were achieved from low cell density ($10 5 cell Á mL À1 ), indicating the role of physical cross-links to mediate aggregation and chondrogenesis. While beyond the scope of this study, other factors, e.g., gel mechanical properties, diffusion of matrix molecules, might have also influenced the chondrogenic differentiation because cross-linking of gels are related to these properties.…”
Section: Chondrogenic Differentiation Of Mscs In Gelsupporting
confidence: 48%
“…Although polymer chains are relatively less random in LM-PEG, it cannot influence MSC function in a biomimetic manner which indicates that polymer morphology achieved through physical cross-link is an effective mechanism for polymer chain assembly and for promoting bioactive functionality in MSCs. Cellular aggregation and enhanced chondrogenesis in hydrogel is typically achieved with excessive cell density ($10 6 cell Á mL À1 ); [20,32] in our studies, cellular aggregation in PEG-PU gels were achieved from low cell density ($10 5 cell Á mL À1 ), indicating the role of physical cross-links to mediate aggregation and chondrogenesis. While beyond the scope of this study, other factors, e.g., gel mechanical properties, diffusion of matrix molecules, might have also influenced the chondrogenic differentiation because cross-linking of gels are related to these properties.…”
Section: Chondrogenic Differentiation Of Mscs In Gelsupporting
confidence: 48%
“…The elastic moduli of the hydrogels used in these studies ranges from 2 kPa to 100 kPa 12,14,20,21 , which is comparable to the moduli of chondrocyte PCM, ranging from 10 kPa to 75 kPa 29 . Enhanced stiffness in covalently crosslinked PEG based hydrogels, found to exhibit minimal stress relaxation here, restricted production of sGAG and collagens, distribution of cartilage matrix, and proliferation of chondrocytes 20,21 . However, our work revealed that the impact of stiffness was dependent on hydrogel relaxation.…”
Section: Discussionmentioning
confidence: 65%
“…As previous work has implicated hydrogel stiffness in mediating cartilage matrix formation 20,21,30 , we next examined how altered hydrogel stiffness regulated the effect of relaxation. In hydrogels with an initial elastic modulus of 20 kPa, trends similar to those in 3 kPa gels were observed, with faster relaxation leading to greater areas of type-II collagen and aggrecan deposition as well as higher quantities of secreted collagen and sGAG (Supplementary Fig.…”
Section: Faster Relaxation or Greater Creep Promotes Enhanced Formatimentioning
confidence: 99%
“…Poly(ethylene glycol) diacrylate (PEGDA)-based hydrogels were used in this study for the establishment of the 3D coculture system, due to their widespread use in cartilage tissue engineering, [34][35][36][37] their easily tunable mechanical properties, 38,39 and their ability to significantly resist cell adhesion even in serum-containing culture environments relative to many biomaterials. 34,40,41 This latter property permits desired cell adhesion to be ''programmed'' into the PEGDA network through conjugation of bioactive moieties.…”
Section: Introductionmentioning
confidence: 99%